KEBERLAKUAN ENTRY INTO FORCE PERJANJIAN REGIONAL ASEAN (Studi Kasus pada Implementasi ASEAN MRA on Type Approval for Automotive Products – APMRA) - Maulida, Reza (Ensiklopedia of Journal, 2025)
This study examines the effectiveness of the entry into force (EIF) clause under the ASEAN Mutual Recognition Arrangement on Type Approval for Automotive Products (APMRA). Although Article 20 stipulates that APMRA shall enter into force one year after the submission of instruments of ratification, its implementation has not progressed as expected. The analysis focuses on the underlying causes of this delay, particularly the interpretation of the two EIF requirements. It assesses whether these conditions should be construed as alternative or cumulative, and how misinterpretation may contribute to the hindered enforcement of APMRA at the ASEAN level.Keywords: APMRA, Entry into Force, ASEAN